Analisis Faktor-Faktor yang Mempengaruhi Equity Risk Premium (Studi Perusahaan Property dan Real Estate yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2020) - Rona Nabila Gusrima; Einde Evana; Yunia Amelia; Lindriana sari (Goodwood Publishing, 2022)
This study aims to empirically examine the factors that influence the equity risk premium in companies listed on the IDX. This study uses a data sample of 34 property and real estate companies listed on the Indonesia Stock Exchange with an observation period of 6 years from 2015-2020, which were taken using the purposive sampling method. The variables used in this study are audit tenure, book to market equity ratio, firm size, leverage, and earnings per share. The analytical technique used in this study is linear regression multiple, namely to determine the effect of audit tenure, book to market equity ratio, firm size, leverage, and earnings per share of the equity risk premium. The results showed that statistically the independent variable audit tenure had a positive effect and the book to market equity ratio had a negative effect on the equity risk premium. while the variables of firm size, leverage, and earnings per share have to effect on the equity risk premium.